Corrosion Mechanism of AM50 Magnesium Alloy in Simulated Acid Rain - Liu, Feng; Song, Yingwei; Shan, Dayong; Han, En-Hou (Recent Patents on Corrosion Science, 2013)
The poor corrosion resistance of magnesium alloys is limiting their widespread applications. Some patents and literatures have reported corrosion-resistant magnesium alloys and surface treatment techniques to improve the corrosion resistance. However, these acknowledges are not enough for well understanding the corrosion behavior of magnesium alloys in actual application environments. In this paper, the influence of Cl- on the corrosion rate of AM50 alloy in simulated acid rain (SAR) was studied using electrochemical tests and scanning electronic microscopy (SEM) observation, and then the corrosion mechanism of magnesium alloys in the acid solution was established. The results show that Cl- can accelerate the corrosion of Mg matrix around the AlMn phases in the initial stage of corrosion. The predominant corrosion type of the AM50 alloy is the uniform type of corrosion in SAR. The coverage fraction of Mg(OH)2, MgH2, and the concentration of Mg+ are three key factors influencing the corrosion processes of magnesium alloys in SAR.
Keywords: simulated acid rain (SAR)